2022
DOI: 10.21203/rs.3.rs-2336569/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contribution of Results-Based Financing in Quality improvement of Health Services at Primary Healthcare Facilities: Findings from Tanzania Star Rating Assessment

Abstract: Background Performance-based financing (PBF) is an important mechanism for improving the quality of health services in low- and middle- income countries. In 2014, Tanzania launched a country-wide quality approach known as Star Rating Assessment (SRA) aims to assess the quality of healthcare service delivery in all Primary Health Care (PHC) Facilities in the country. Furthermore, by 2015, the country rolled out RBF initiatives into eight regions in which PHC facilities were paid incentives based on their level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The results showed that the clients/patients took a total average of more than 2 hours in most of the clinics to wait for service being attended by the nurse and doctor at the respective clinic/Emergency Medicine Department. This was contradictory to the star rating performance of the Ministry of Health which insists the total waiting time from arrival time until time seen by health worker/doctor should be less than 60 minutes (12), (10). The study which was done in India also differentiated from the current study since more than three-quarters of participants appreciated that the waiting time to be attended by the doctor was less than 60 minutes (13) Also, in the areas in which the patients took more minutes to wait for services/wait to be seen by the Doctor, in these areas the patients took more than 80 minutes.…”
Section: Discussionmentioning
confidence: 84%
“…The results showed that the clients/patients took a total average of more than 2 hours in most of the clinics to wait for service being attended by the nurse and doctor at the respective clinic/Emergency Medicine Department. This was contradictory to the star rating performance of the Ministry of Health which insists the total waiting time from arrival time until time seen by health worker/doctor should be less than 60 minutes (12), (10). The study which was done in India also differentiated from the current study since more than three-quarters of participants appreciated that the waiting time to be attended by the doctor was less than 60 minutes (13) Also, in the areas in which the patients took more minutes to wait for services/wait to be seen by the Doctor, in these areas the patients took more than 80 minutes.…”
Section: Discussionmentioning
confidence: 84%